Positive communication workshops: are they useful for treatment programmes for anorexia nervosa? - Tchanturia, Kate; Croft, Philippa; Holetic, Victoria; Webb, Jessica; Dapelo, Marcela Marin (Frontiers in Psychology, 2023)
Background: Social isolation, loneliness and difficulties in relationships are often described as a core feature of eating disorders.Based on the experimental research, we have designed one-off workshops for patients in inpatients and day care services and evaluated its acceptability and effectiveness using feedback questionnaires.Methods: This naturalistic project is an evaluation of multiple positive communication workshops. Forty-one participants completed workshop questionnaires, which were provided immediately at the beginning and end of the workshop, including feedback on these one-off groups. The workshops consisted of educational and experiential components. The questionnaire outcomes were evaluated by independent researchers.Results: All participants were female adults with a mean age of 33 (12.2) and a diagnosis of Anorexia Nervosa (AN; either restrictive or binge-purge subtype). Post-workshop questionnaires showed large effect sizes in the improvement of understanding the importance and confidence in using positive communication strategies.Discussion: Addressing social communication difficulties in eating disorder treatment programmes adds valuable dimensions to these symptom-based treatments in both inpatient settings and day services, and may provide broader benefits in overall social functioning in patients with AN.Brief one-off workshops targeting social functioning for patients with eating disorders might be useful complementary input for treatment programmes.